Regeneração natural e banco de sementes do solo em um gradiente altitudinal de Floresta Ombrófila Densa - Abreu, Vítor de Souza (2017)
To understand natural regeneration as a process of species conservation in the ecosystem, it is necessary to understand the mechanisms that allow the entry of new individuals into the forest community and the influence exerted by environmental variables on the distribution of these species. Therefore, this study aimed to investigate the influence of environmental variables on the structure of natural regeneration and analyze the composition of the soil seed bank and its floristic relationships with the regenerating and adult strata of the community, as well as with seed rain along an altitudinal gradient. The study was carried out in the Santa Marta valley, south of the Caparao National Park, located on the border of the states of Espirito Santo and Minas Gerais. During previous studies, seven permanent plots were demarcated along the valley at different altitudinal quotas. For sampling of natural regeneration and seed bank, four subplots (2 x 20 m) were systematically allocated adjacent to each of the seven plots. In each subplots, height and diameter at ground height (DAS) data were recorded of individuals in height > 50 cm and diameter at 1.30 m above the ground (DAP) < 2.5 cm; and at two seasons of the year (rainy and dry seasons) samples of the first 8 cm of soil were collected. These samples were kept in a greenhouse for six months, where monthly evaluations of the number of germinated seeds were carried out. Data from seed rain and the adult component were obtained from previous studies. In addition to the vegetation data, several environmental and spatial variables (MEMs - Moran’s Eigenvector Maps) were evaluated. The floristic similarity between the quotas was analyzed based on the Bray-Curtis similarity index, using UPGMA cluster analysis. Redundancy Analysis (RDA) was performed to verify the influence of environmental and spatial factors on regenerating vegetation; and the Non-metric Multidimensional Scaling (NMDS), to analyze the floristic relationships in the forest stretch under study. Both for natural regeneration and for the seed bank, the higher elevations (1.420 to 1.550 m a.s.l.) were floristically more similar to each other than with the lower quotas (1.112 to 1.391 m a.s.l.). It was verified that the pattern of species substitution occurred due to environmental variables (litter accumulation and potential soil acidity) and the spatial variable MEM 15, with the first three RDA axes explaining an accumulated 60.1% of the variation in the floristic composition of the regenerating community. Finally, there was a floristic distancing of the seed bank in relation to seed rain, atural regeneration and adult vegetation in all altimetric quotas, mainly due to the predominance of pioneer species. These results confirm that some species have environmental preferences along the gradient and that the joint action of environmental and spatial variables are important predictors of the distribution of regenerating species. It is also concluded that the seed bank is an important mechanism to recompose the vegetal cover after eventual disturbances, because it is composed mainly of species of initial stages of succession.